2018
DOI: 10.1084/jem.20172244
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal integrity and complement control synaptic material clearance by microglia after CNS injury

Abstract: Norris et al. show that microglia are the key phagocytes in removal of synaptic debris in the dorsal lateral geniculate nucleus after optic nerve injury. This microglial function is dependent on recognition of neurodegeneration and is mediated by the complement system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 70 publications
4
72
0
Order By: Relevance
“…The increased iC3b deposition in the ONL upon the onset of photoreceptor degeneration, elevated retinal expression of Cd11b , a component of the CR3, and the ONL translocation of CR3-expressing microglia, point to increased microglia–photoreceptor interactions via iC3b-CR3 binding ( Bajic et al, 2013 ; Xu et al, 2017 ) as part of an adaptive complement response. C3–CR3 interaction has been previously demonstrated as a molecular mechanism employed by microglia to eliminate supernumerary synapses during normal brain development ( Stevens et al, 2007 ) and to clear synaptic debris following injury-induced synaptic degeneration ( Norris et al, 2018 ), but which may drive maladaptive phagocytosis of synapses in certain CNS pathologies ( Berg et al, 2012 ; Hong et al, 2016 ). Additionally, iC3b-CR3 function in microglia has also been shown to mediate beneficial clearance of apoptotic neurons ( Elward and Gasque, 2003 ) and extracellular debris ( Fu et al, 2012 ; Hadas et al, 2012 ) following neural injury via phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The increased iC3b deposition in the ONL upon the onset of photoreceptor degeneration, elevated retinal expression of Cd11b , a component of the CR3, and the ONL translocation of CR3-expressing microglia, point to increased microglia–photoreceptor interactions via iC3b-CR3 binding ( Bajic et al, 2013 ; Xu et al, 2017 ) as part of an adaptive complement response. C3–CR3 interaction has been previously demonstrated as a molecular mechanism employed by microglia to eliminate supernumerary synapses during normal brain development ( Stevens et al, 2007 ) and to clear synaptic debris following injury-induced synaptic degeneration ( Norris et al, 2018 ), but which may drive maladaptive phagocytosis of synapses in certain CNS pathologies ( Berg et al, 2012 ; Hong et al, 2016 ). Additionally, iC3b-CR3 function in microglia has also been shown to mediate beneficial clearance of apoptotic neurons ( Elward and Gasque, 2003 ) and extracellular debris ( Fu et al, 2012 ; Hadas et al, 2012 ) following neural injury via phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Complement has also been implicated in microglial elimination of synapses in AD, mediating pathological loss of synapses in AD mouse models (Hong et al, 2016;Shi et al, 2017). Complement is also involved in synaptic loss in response to acute brain injury (Alawieh, Langley, Weber, Adkins, & Tomlinson, 2018;Norris et al, 2018), chronic tau accumulation (Dejanovic et al, 2018), epilepsy (Wyatt, Witt, Barbaro, Cohen-Gadol, & Brewster, 2017), neuroinflammation (Watkins et al, 2016), and other disease contexts (Sekar et al, 2016). Other microglial signaling components also have important functions in both brain development and neurodegeneration, including CX3CR1 (Basilico et al, 2019;Paolicelli et al, 2011;Sheridan & Murphy, 2013) and progranulin (Baker et al, 2006;Lui et al, 2016), further illustrating that common mechanisms can mediate important microglial functions in brain health and disease (Tenner, Stevens, & Woodruff, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the other genes including Kdr , S1pr1 , Ubc , Grm2 , Pdyn , and Itgam are possible candidates for ASD due to the related molecular functions. For examples, S1pr1 regulates multiple aspects of sensory neuron and immune system functions [Healy & Antel, ]; Ubc encodes a ubiquitin C and participates in neuronal development and maintenance; Grm2 is associated with depression and memory network related to glutamatergic synapse [Jin et al, ; Lyon et al, ]; Pdyn encodes a prodynorphin, which is closely related to drug abuse and synaptic plasticity [Henriksson et al, ]; and Itgam has been reported to be involved in the debris clearance of microglia [Norris et al, ]. Therefore, it is possible that the misregulation of these genes contributes to certain phenotypes of ASD.…”
Section: Discussionmentioning
confidence: 99%